Model and experimental development for Business Data Science. Issue 4 (August 2016) - Newman, Russell; Chang, Victor; Walters, Robert John; Wills, Gary Brian
Highlights: We investigate the impacts of Data Science for businesses. We present the Business Data Science (BDS) model. We demonstrate the details for the BDS model and confirm its validity, usefulness and readiness for organisational adoption. We provide a guideline for organisaitons to consider adoption while applying recommendations from BDS model. Abstract: While Data Science has become increasingly significant for business strategies, operations, performance, efficiency and prediction, there is little work on this to provide a detailed guideline. We have proposed a Business Data Science (BDS) model that focuses on the model and experimental development that allows different types of functions, processes and roles to work together collaboratively for efficiency and performance improvements. Details with examples have been illustrated to show that BDS model can be a robust model. Future directions have been discussed to ensure that business intelligence, security, analytics and research contributions to BDS can be achieved.